Communication, Credible Improvements and the Core of an Economy with Asymmetric Information - Oscar Volij (Brown University, Department of Economics, 1997)
We analyze an economy with asymmetric information and endogenize the possibilities for information transmission between members of a coalition. We then define a concept of the Core that takes into account these communication possibilities. The internal consistency of the improvements is considered and an Internally Consistent Core is introduced, that requires credibility from the improvements.
Keywords: 330